RISK ANALYSIS STUDY OF NOx, and SOx FROM TRANSPORTATION (CASE STUDY: MAIN STREETS OF D.I. JOGJAKARTA) - Mochamad Arief Budihardjo (TEKNIK, 2007)
The air pollution problems have been progressively set attention to the world especially industrialcountries recently. These problems not only give affect at health like emphysema, bronchitis, and otherinhalation disease but also make plants and properties destruction causes very big loss. This research isconcerned with the risk level which is accepted by people who reside in roadside because most of airpollutants come from transportation facilities such as motor vehicle. The limitation of the research is airpollutants exposure such like NOx, and SOx which enter the body through respiration. This risk analysisresearch is broken down into four step as follow; hazard identification showing NO2, and SO2concentration in 15 sampling locations where the highest value of NO2 is 56,5 μg / m3 and SO2 is 28,87μg/m3. According to DIY Governor Regulation No. 153 Year 2002 about the value of ambient air qualitystandard, quality standard of NO2 is 400 μg / m3, and SO2 is 900 μg / m3. It can be concluded thatconcentration of NO2 and SO2 in 2005 within all sampling locations is still under of quality standard. Thestep of exposure assessment involves the exposed population including pedicab worker, park worker, andcloister merchant. From calculation, the intake range of NO2 enters the body is 0,0025-0,0075 mg/kg.dayand SO2 is 0,0008-0,0038 mg/kg.day. Third step is dose-response assessment to find out what will be facedby people if exposure of pollutants occurs in a certain dose. The last step is risk characterization, theresult of research is that risk value / Hazard Index (HI) less than 1 that still acceptable. It can besummarized that the ambient air quality of Jogjakarta especially NO2 and SO2 gas do not too adverse tohealth.